2015
DOI: 10.1002/polb.23910
|View full text |Cite
|
Sign up to set email alerts
|

The influence of short-chain branching on the morphology and structure of polyethylene single crystals

Abstract: The influence of short‐chain branching on the formation of single crystals at constant supercooling is systematically studied in a series of metallocene catalyzed high‐molecular‐weight polyethylene samples. A strong effect of short‐chain branching on the morphology and structure of single crystals is reported. An increase of the axial ratio with short‐chain branching content, together with a characteristic curvature of the (110) crystal faces are observed. To the best of our knowledge, this is the first time t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 86 publications
(235 reference statements)
6
19
0
Order By: Relevance
“…In this simulation of branched polyethylene crystallization, the crystal configuration was lamellae crystal for MSL of 50 CH 2 and bundle crystal for that of 34 CH 2 . Vega et al observed the single crystal in orthorhombic form of metallocene catalyzed butyl branched polyethylene with BC from 0 to 10/1000 C. The crystal configuration was also single lamellae crystal form for BC below 10/1000 C in this simulation. The critical MSL mentioned above for lamellae thickness was 50 CH 2 (20/1000 C) in the butyl branching polyethylene crystallization .…”
Section: Resultssupporting
confidence: 64%
“…In this simulation of branched polyethylene crystallization, the crystal configuration was lamellae crystal for MSL of 50 CH 2 and bundle crystal for that of 34 CH 2 . Vega et al observed the single crystal in orthorhombic form of metallocene catalyzed butyl branched polyethylene with BC from 0 to 10/1000 C. The crystal configuration was also single lamellae crystal form for BC below 10/1000 C in this simulation. The critical MSL mentioned above for lamellae thickness was 50 CH 2 (20/1000 C) in the butyl branching polyethylene crystallization .…”
Section: Resultssupporting
confidence: 64%
“…The solutions were then recrystallised to obtain single crystals at four temperatures (T c = 73 °C, 68 °C, 63 °C and 58 °C) below T s during 24 hours. At this degree of supercooling almost the whole material crystallizes in 1,2,4trichlorobenzene during the CRYSTAF experiments (2-3 hours) at a cooling rate of 0.1 °C•min -1 [13]. Then, it is expected that the isothermal crystallization experiments performed in p-xylene during 24 hours avoided fractionation of the sample and depleted almost the whole dissolved material.…”
Section: Methodsmentioning
confidence: 98%
“…The molecular and physical properties were obtained by 13 C-Nuclear Magnetic Resonance, Size Exclusion Chromatography and CRYSTAF-TREF analysis. Please refer to previous works for details about molecular and physical characterization [13,[17][18][19][20][21][22].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the recent years, many studies have established that physical properties of polymers are governed by the chemical structure and the molecular architecture, especially the influence of short chain branching (SCB). [1][2][3][4][5][6][7][8][9][10] By "short," it is here referred as a branch with a molecular weight far lower than the entanglement molecular weight, M e that is usually more than 1 kg mol −1 . [11] In a number of (2 of 11) 1700005 density and the rheological properties of polymers.…”
Section: Introductionmentioning
confidence: 99%